ANALISIS MODEL PEMBELAJARAN KOLABORATIF BERBASIS DEEP LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP IPAS PESERTA DIDIK KELAS V SD NEGERI BANYUANYAR 1 SURAKARTA - Sofiyani Nur Amali; Oktiana Handini; Sarafuddin, Sarafuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to: 1) examine the effectiveness of a collaborative learning model based on deep learning, and 2) explore how collaborative interaction shapes meaningful learning experiences for fifth-grade students. This research employs a descriptive qualitative approach. The data sources consist of primary and secondary data. The research subjects include the principal, the fifth-grade teacher, and fifth-grade students, with the object of the study being the analysis of a deep learning–based collaborative learning model in improving students’ conceptual understanding of IPAS (Integrated Science and Social Studies) at SD Negeri Banyuanyar 1 Surakarta. Data collection techniques used in this study were observation, interviews, and documentation. Data validity was ensured through source triangulation and technique triangulation. The data analysis procedures included data collection, data reduction, data display, and conclusion drawing. Based on the research findings, it can be concluded that: 1) the collaborative learning model enhances students’ active engagement in the learning process through discussion activities, task distribution, pop-up creation practices, presentations, and question-and-answer sessions; and 2) collaborative interactions developed during the learning process play a significant role in shaping meaningful learning experiences for fifth-grade students.